Revisiting the Confucian Objections to Beauchamp and Childress’ Principle of Respect for Autonomy - Tan, Charlene; Neo, Ruth (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
A persistent Confucian critique of Beauchamp and Childress’ principle of respect for autonomy is that the principle exalts individual autonomy and ignores family-based medical decision-making. This article defends the principle by questioning its individualistic underpinnings and arguing that it is compatible with family-based medical decision-making through specification.